Endocannabinoid-Mediated Control of Neural Circuit Excitability and Epileptic Seizures - Sugaya, Yuki; Kano, Masanobu (Frontiers in Neural Circuits, 2022)
Research on endocannabinoid signaling has greatly advanced our understanding of how the excitability of neural circuits is controlled in health and disease. In general, endocannabinoid signaling at excitatory synapses suppresses excitability by inhibiting glutamate release, while that at inhibitory synapses promotes excitability by inhibiting GABA release, although there are some exceptions in genetically epileptic animal models. In the epileptic brain, the physiological distributions of endocannabinoid signaling molecules are disrupted during epileptogenesis, contributing to the occurrence of spontaneous seizures. However, it is still unknown how endocannabinoid signaling changes during seizures and how the redistribution of endocannabinoid signaling molecules proceeds during epileptogenesis. Recent development of cannabinoid sensors has enabled us to investigate endocannabinoid signaling in much greater spatial and temporal details than before. Application of cannabinoid sensors to epilepsy research has elucidated activity-dependent changes in endocannabinoid signaling during seizures. Furthermore, recent endocannabinoid research has paved the way for the clinical use of cannabidiol for the treatment of refractory epilepsy, such as Dravet syndrome, Lennox-Gastaut syndrome and tuberous sclerosis complex. Cannabidiol significantly reduces seizures and is considered to have comparable tolerability to conventional antiepileptic drugs. In this article, we introduce recent advances in research on the roles of endocannabinoid signaling in epileptic seizures and discuss future directions.